2019
DOI: 10.2134/jeq2019.02.0042
|View full text |Cite
|
Sign up to set email alerts
|

Cropland Amendment with Beef Cattle Manure Minimally Affects Antimicrobial Resistance

Abstract: Concerns exist that beef cattle manure amendment may increase antimicrobial resistance (AMR) in cropland soils and persist over time, potentially increasing food-animal and human exposure via feed and produce. Manure and soil contain many types of antibiotic-resistant bacteria. However, zoonotic pathogens and fecal indicators are most directly linked to human disease and environmental surveillance efforts. We measured the levels of eight antimicrobial resistant zoonotic pathogens and fecal indicators at experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The authors (Miller et al, 2019) also noted that the effect dissipated in spring, summer, and harvest samplings. The evidence clearly shows that animal manure soil amendment temporarily increases generic and antimicrobial-resistant E. coli strains in the soil.…”
Section: Discussionmentioning
confidence: 93%
“…The authors (Miller et al, 2019) also noted that the effect dissipated in spring, summer, and harvest samplings. The evidence clearly shows that animal manure soil amendment temporarily increases generic and antimicrobial-resistant E. coli strains in the soil.…”
Section: Discussionmentioning
confidence: 93%
“…Repeated long‐term manure application has also been observed to enrich for ARGs (Tang et al., 2015; Li et al., 2017; Guo et al., 2018; Rahman et al., 2018; Wang et al., 2020), though results are inconsistent likely because of differences in soil types and management and the specific ARGs studied. Further, when assessing AMR in the form of resistant zoonotic pathogens and fecal indicator organisms, beef manure application to soils did not result in higher levels of detection and only ermB and tetM persisted after planting occurred (Miller et al., 2019), again highlighting the need for comprehensive monitoring of appropriate indicators to inform risk assessment. Even if animal producers decrease or abandon the use of antibiotics, detectible ARGs may persist for decades, and it is currently unclear what the risks of these impacts would be for human health (Pruden et al., 2013).…”
Section: Transport Of Amr Indicators Into Soil and Watermentioning
confidence: 99%
“…Once in the environment, antibiotics can exert selection pressure on bacteria (Pruden et al, 2006) resulting in the propagation and spread of ARB via hydrologic processes beyond the point of use, consequently resulting in environmental and public health concerns (Peak et al, 2007). Antibiotic resistant bacteria can cause severe, difficult to treat, and sometimes fatal infections, with groundwater serving as a potential source of antimicrobial resistant pathogens in the human food chain (Chee-Sanford et al, 2001;Campagnolo et al, 2002) or when animal manure is land applied as soil amendment (Miller et al, 2019). Several studies reported multiple ARGs in various environments including water, sludge, farm soils, sediment, animal manure, and municipal wastewater (Chen et al, 2010;Knapp et al, 2010;Munir and Xagoraraki, 2011;Jiang et al, 2013;Agga et al, 2015aAgga et al, , 2019Rodriguez-Mozaz et al, 2015;Sui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Manure from livestock and poultry farming plays an important role in the dissemination of ARB and ARGs in the environment when applied as fertilizer on agricultural farms. Manure is a reservoir of ARB and antibiotic compounds, and its application on agricultural soils can significantly increase ARGs and selects for ARB populations in the farm soils and other environmental compartments (Heuer et al, 2011;Udikovic-Kolic et al, 2014;Miller et al, 2019;Meyers et al, 2020). Cattle and swine manure storage lagoons are known to carry ARGs including various tetracycline resistance (tet) genes (Koike et al, 2007;Peak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%